Public Sector Research Priorities for Sustainable Food Security: Perspectives from Plausible Scenarios - Nelson, Gerald C.; Mensbrugghe, Dominique van der (2013)
Public Sector Research Priorities for Sustainable Food Security by Gerald Nelson, IFPRI and Dominique van der Mensbrugghe, FAO at the Food Security Futures I Conference, on 11 April 2013 in Dublin, Ireland.